Revisiting Energy and Governmental Funds Allocation in Pakistan: A Novel Zero-Sum Gain DEA Approach - Nadeem Iqbal; Qaiser Abbas; Mukhtiar Ali Erri; Dr. Shams ur Rehman (Journal of Business & Tourism, 2021)
Like many developing countries, Pakistan has limited energy production and governmental funding to support its development. This research focuses on energy efficiency levels and governmental funds distribution among four provinces in Pakistan. Based on balanced panel data from 2006 to 2016, this study develops a novel Zero-Sum Gain (ZSG) DEA approach to simultaneously assess energy efficiency levels and reallocate limited financial resources among provinces. Under the assumption of constant outputs, energy production and governmental funds are considered as input variables, while GDP and population as output variables. Results indicate that efficiency levels of Pakistan provinces range between 0.62 to 0.88, thus suggesting room for improvement in funding allocation.